2018
DOI: 10.3389/fpsyg.2018.02071
|View full text |Cite
|
Sign up to set email alerts
|

Groups and Emotional Arousal Mediate Neural Synchrony and Perceived Ritual Efficacy

Abstract: We present the first neurophysiological signatures showing distinctive effects of group social context and emotional arousal on cultural perceptions, such as the efficacy of religious rituals. Using a novel protocol, EEG data were simultaneously recorded from ethnic Chinese religious believers in group and individual settings as they rated the perceived efficacy of low, medium, and high arousal spirit-medium rituals presented as video clips. Neural oscillatory patterns were then analyzed for these perceptual j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 69 publications
1
4
0
1
Order By: Relevance
“…Hanslmayr et al reported that the power and phase synchrony in alpha-band were decreased for enhanced sensory processing due to externally oriented states [36]. Consistently with our results on inter-regional functional connectivity, Cho et al showed significant decrease of alpha-band phase locking value due to the higher arousal level of rituals [37].…”
Section: Alpha-band Desynchronization For Attentional Processingsupporting
confidence: 91%
“…Hanslmayr et al reported that the power and phase synchrony in alpha-band were decreased for enhanced sensory processing due to externally oriented states [36]. Consistently with our results on inter-regional functional connectivity, Cho et al showed significant decrease of alpha-band phase locking value due to the higher arousal level of rituals [37].…”
Section: Alpha-band Desynchronization For Attentional Processingsupporting
confidence: 91%
“…Future research could explore the neural substrates of the self-defining group experiences proposed to be critical for fusion via the shared-experience pathway. For instance, when adult believers watched videos of religious rituals, a group setting induced neural synchrony among watchers—social tuning effects—as measured by theta-phase synchrony from electroencephalography data (Cho et al, 2018). Perhaps the study of neural substrates could even differentiate between the heightened sense of self proposed with fusion and the subsumed sense of self with group identification better than the current self-report measures (see Apps et al, 2018).…”
Section: Methodological Challenges For Research On the Development Of...mentioning
confidence: 99%
“…Paying attention to the socio-environmental context of these shared experiences may therefore be key to understanding how group cohesion comes about. For example, does sharing an event revolve around attending to the same stimuli and thus imagining that one’s emotions and thoughts are shared with others, or does it also involve more fundamental adjustments, such as the inter-personal synchronization of physiological states 30 ? Further, how is this synchronization affected by sharing the experience directly, by being physically co-present, as opposed to indirectly or vicariously, by observing the same event remotely?…”
Section: Introductionmentioning
confidence: 99%